Desenvolvimento de metodologia para determinação de resíduos de inseticidas em coleiras ectoparasiticidas - Gomes, Pricília Santos Pereira (2022)
Ectoparasiticidal collars are used in dogs and cats with the purpose of zoonoses controlling, acting as a repellent and/or killing effect in vectors. The contact of animals or people with pesticides can cause intoxication, with ectoparasiticidal collars could be a source because linked to more than 76,000 incidents in dogs and people in the United States. This work aimed to develop a method for the determination of insecticides residues of the propoxur, dichlorvos, diazinone, chlorpyrifos, deltamethrin, and flumethrin present in commercial ectoparasiticidal collars with Liquid chromatography/mass spectrometry and ultrasound-assisted extraction. In the optimized condition, the analytes were extracted with 10 mL of acetonitrile for 45 min on ultrasound, showing recovery values (30±6 and 103±8%) in a concentration range of 0.005 to 1.0 mg L-1 . Under optimal conditions, good linearity and sensitivity were obtained in a range of 0.005 to 5.0 mg L-1 with coefficients of determination above 0.99. The relative standard deviations for triplicate determinations were less than 24% and the limits of detection and quantification were in the range of 0.0004– 0.0409 mg L-1 and 0.0011–0.1240 mg L-1 , respectively. The method proposed was applied to the Seresto® collar after a period of action, where residues of the insecticides imidacloprid and flumethrin were found.